Horner's syndrome secondary to tube thoracostomy - Özel, SK; Kazez, A (Turkish J Pediatrics, 2004)
Tube thoracostomy is a common therapeutic approach applied in medical practice. Certain complications of this procedure have been described in the literature. Oculosympathetic paresis, or Homer's syndrome, occurs from the interruption of second order preganglionic neurons and manifests as miosis, ptosis, hemifacial anhidrosis and enophthalmos. Iatrogenic Horner's syndrome, on the other hand, very rarely couples with tube thoracostomy. Only seven cases have been described in the literature, two of whom were in the pediatric age group. Herein we present a three-year-old girl operated for diaphragmatic hernia who later developed Homer's syndrome at the same side of the thorax tube. Upon the development of the pathology, the tube was repositioned and after one month only a slight ptosis persisted. Our patient seems to be the third case described in the literature. The clinical significance of this pathology is assessed in this report.
Keywords: tube thoracostomy; Horner's syndrome